Conjunctive Queries with Negations: Bridging Theory and Practice - Li, Boyi (University of Waterloo, 2025)
Antijoin, given its significant expressive power, has numerous applications in relational data analytics. Notwithstanding its importance, there remains great research potential in antijoin processing. In practical database systems, existing techniques to process antijoins are still considered rudimentary, building upon heuristics and cost-based optimization strategies that offer no theoretical guarantees. Meanwhile, the database theory community has proposed algorithms for antijoins with strong theoretical guarantees, yet these algorithms build upon specialized, complicated data structures and have not made their way to practice. In light of such gap between theory and practice, we propose new algorithms for antijoin processing in this thesis. Not only do our new algorithms provide the same theoretical guarantees as the state-of-the-art algorithm, but they also use only basic relational operations. The latter property enables our new algorithms to be rewritten in basic SQL statements, allowing an easy, system-agnostic integration into any SQL-based database system. We then empirically evaluate one of our new algorithms, rewritten in SQL, over real-life graph datasets with a variety of SQL database systems. Experimental results show order-of-magnitude improvements of our new algorithm over vanilla SQL queries.
Keywords: antijoin processing; query rewrite; relational algorithm; counting